Batch production of 6-inch uniform monolayer molybdenum disulfide catalyzed by sodium in glass - Pengfei Yang (Nature Portfolio, 2018)
Growth of large-area monolayer transition metal dichalcogenides is critical for their application but remains challenging. Here Yang et al. report rapid chemical vapor deposition of 6-inch monolayer molybdenum disulfide by sufficiently uniformly supplying the precursors and catalysts.